Relações de gênero no exercício da coordenação pedagógica - Sales, Juliana Azevedo Campos (2015)
The objective of this work is to analyse if male domination determines the work of men and women as pedagogical coordinators; and, as long this situations is confirmed, to understand how it happens at schools. The hypothesis is that male domination, considered as an habitus‟ disposition, makes men and women work and recognize their work in different ways. It‟s an exploratory research which aims to obtain a deeper understanding of gender questions on pedagogical coordination. The research was developed at the Goiás state‟s public educational service, by the analysis of the pedagogical coordinators‟ responses to a survey. The main theoretical references were Pierre Bourdieu‟s works on gender and male domination; Michaël Huberman‟s studies on teacher‟s life cycle; and Flávia Vieira‟s works on pedagogical coordination. The results shows that male domination produces differences on men‟s and women‟s careers, and it also naturalizes the differences of their professional skills; in other hand, the data also shows that the training of pedagogical coordinator by the public educational services can produce effects over the homogenization of the perceptions of men and women about their work